Clitoral length in immature and mature captive tufted capuchin (Sapajus spp.) females: A cross‐sectional study. Issue 11 (22nd April 2020) - Carosi, Monica; Spani, Federica; Ulland, Amy E.; Scalici, Massimiliano; Suomi, Stephen J.
Abstract: Quantitative data on female external genital morphology are sporadic in the primate literature, and the intraspecific and interfemale variation is especially under investigated (e.g., external clitoris length). Since in most anthropoid primate species female external genitals are relatively small and often hidden, for those species whose external clitoris is described as hypertrophic, external genital resemblance may represent a source of confusion in distinguishing the sexes at a distance. This is the case of both captive and wild tufted capuchin ( Sapajus spp.) infants. We provided data on external clitoral length and investigated differences in this trait at different ages in a captive female tufted capuchin population. Since likely allometric growth describes changes in relative dimensions of parts of the body that are correlated with changes in overall size, clitoris length has been analyzed by using body weight as a covariate. We measured clitoral length by adapting a technique developed for spotted hyenas ( Crocuta crocuta ). Our results suggest that the small body size may be only in part responsible of the perception of long clitoris in female infants, since the clitoris is actually longer in immature females compared to adult ones and its size is inversely related to body weight. While the cross‐sectional nature of these data does not allow for conclusive interpretation of the results, we tentatively suggest this phenomenon as a transient male‐mimicry by immature females. Our study contributed to the description of normative data in a clitoral trait, thus providing foundation for future studies about causal mechanisms and possible adaptive function(s). Abstract : In Sapajus it may be difficult to sex infants at a distance due to the external genitals which in immatures may represent a source of confusion. The human perception of a longer external clitoris in immature than mature females may only in part be explained by different body proportions, since our results suggests that length of the external clitoris is actually larger in infants (I) and juveniles (J) than in adults (A). Longer external clitoris in immature compared to mature females may tentatively be interpreted as a transient male‐mimicry. Research Highlights: The external clitoris length of tufted capuchin monkeys is larger in infants and juveniles than in adults. Longer external clitoris in immature compared to mature females may tentatively be interpreted as a transient male‐mimicry by immature females.